Neuronal deletion of phosphatase and tensin homolog in mice results in spatial dysregulation of adult hippocampal neurogenesis - Latchney, Sarah E.; Ruiz Lopez, Brayan R.; Womble, Paige D.; Blandin, Katherine J.; Lugo, Joaquin N. (Frontiers in Molecular Neuroscience, 2023)
Adult neurogenesis is a persistent phenomenon in mammals that occurs in select brain structures in both healthy and diseased brains. The tumor suppressor gene, phosphatase and tensin homolog deleted on chromosome 10 (Pten) has previously been found to restrict the proliferation of neural stem/progenitor cells (NSPCs) in vivo. In this study, we aimed to provide a comprehensive picture of how conditional deletion of Pten may regulate the genesis of adult NSPCs in the dentate gyrus of the hippocampus and the subventricular zone bordering the lateral ventricles. Using conventional markers and stereology, we quantified multiple stages of neurogenesis, including proliferating cells, immature neurons (neuroblasts), and apoptotic cells in several regions of the dentate gyrus, including the subgranular zone (SGZ), outer granule cell layer (oGCL), molecular layer, and hilus at 4 and 10 weeks of age. Our data demonstrate that conditional deletion of Pten in mice produces successive increases in dentate gyrus proliferating cells and immature neuroblasts, which confirms the known negative roles Pten has on cell proliferation and maturation. Specifically, we observe a significant increase in Ki67+ proliferating cells in the neurogenic SGZ at 4 weeks of age, but not 10 weeks of age. We also observe a delayed increase in neuroblasts at 10 weeks of age. However, our study expands on previous work by providing temporal, subregional, and neurogenesis-stage resolution. Specifically, we found that Pten deletion initially increases cell proliferation in the neurogenic SGZ, but this increase spreads to non-neurogenic dentate gyrus areas, including the hilus, oGCL, and molecular layer, as mice age. We also observed region-specific increases in apoptotic cells in the dentate gyrus hilar region that paralleled the regional increases in Ki67+ cells. Our work is accordant with the literature showing that Pten serves as a negative regulator of dentate gyrus neurogenesis but adds temporal and spatial components to the existing knowledge.